2017
DOI: 10.1186/s12981-017-0169-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex hormones and the vaginal microbiome in susceptibility and mucosal immunity to HIV-1 in the female genital tract

Abstract: While the prevalence of Human immunodeficiency virus-1 (HIV-1) infection has stabilized globally, it continues to be the leading cause of death among women of reproductive age. The majority of new infections are transmitted heterosexually, and women have consistently been found to be more susceptible to HIV-1 infection during heterosexual intercourse compared to men. This emphasizes the need for a deeper understanding of how the microenvironment in the female genital tract (FGT) could influence HIV-1 acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…In a similar vein, studies have shown that women with bladder issues such as urge urinary incontinence have more diverse bladder microbiomes than women without incontinence (69,70). Additionally, studies have shown that women with imbalances in Lactobacillus in their vaginal microbiome can have changes in hormones associated with cervicovaginal inflammation, which leads to changes in their vaginal immunity and HIV susceptibility (10,57,71). It is possible that the handling and stress of the study contributed to an increase in the microbiome diversity for Control animals, and that the three Treatment rats with lower rate of increase or a decrease were affected by stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, studies have shown that women with bladder issues such as urge urinary incontinence have more diverse bladder microbiomes than women without incontinence (69,70). Additionally, studies have shown that women with imbalances in Lactobacillus in their vaginal microbiome can have changes in hormones associated with cervicovaginal inflammation, which leads to changes in their vaginal immunity and HIV susceptibility (10,57,71). It is possible that the handling and stress of the study contributed to an increase in the microbiome diversity for Control animals, and that the three Treatment rats with lower rate of increase or a decrease were affected by stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…As noted before, the distinct anatomical regions of the FGT respond differentially to the presence of endogenous hormones, and therefore making direct comparisons between different tissue types will expectedly result in divergent observations. Moreover, in the analysis of human CVL samples, several confounding factors that influence the immune microenvironment of the FGT, such as the indigenous microbiome and the presence of other STIs, could likewise affect observations . This is supported by a recent study, in which the degree of inflammatory fluctuations across the menstrual cycle was dependent on vaginal microbiome composition .…”
Section: Mechanisms Of Hormonal‐mediated Hiv‐1 Susceptibilitymentioning
confidence: 83%
“…The epithelium in the upper genital tract (UGT) is lined by a monolayer of columnar cells that form tight junctions, and therefore, HIV‐1 translocation could occur easily if this barrier is disrupted. In addition, an abundance of target cells, such as CD4+ T cells, and macrophages can be present underneath the epithelium in the endocervix . Although the lower genital tract (LGT) is better protected because of the existence of multiple layers of squamous epithelial cells, the LGT has a much larger surface area compared to the UGT, and the LGT is the site which is in direct contact with semen ejaculate containing infectious virus.…”
Section: Hiv‐1 and Epithelial Barriermentioning
confidence: 99%
“…During a woman's reproductive years, the fluctuating levels of hormones that regulate the menstrual cycle are an important influence on the vaginal microbiome, especially the estradiol (E2) and progesterone (P) . The levels of sex hormones would affect the components of the female genital tract defensive barriers, including the mucous viscosity, epithelial barrier thickness, immune cell frequency, and resident vaginal microbes …”
Section: Introductionmentioning
confidence: 99%
“…3,4 The levels of sex hormones would affect the components of the female genital tract defensive barriers, including the mucous viscosity, epithelial barrier thickness, immune cell frequency, and resident vaginal microbes. 3,5 Previous studies have explored the physiological interaction between sex hormones and vaginal flora. Estrogen promotes hyperplasia and thickening of vaginal epithelia and the increase in glycogen.…”
Section: Introductionmentioning
confidence: 99%